2019
DOI: 10.1177/2333794x19833734
|View full text |Cite
|
Sign up to set email alerts
|

Extension for Community Healthcare Outcomes Uruguay: A New Strategy to Promote Best Primary Care Practice for Autism

Abstract: Introduction . In Uruguay, the special care required for children with neurodevelopmental disorders presents difficulties including lack of access to specialists and rehabilitation services. Project ECHO (Extension for Community Healthcare Outcomes) connects primary care clinicians from remote areas to specialists to enable them to treat complex conditions through ongoing education and mentoring. Objective . To share the experience of the ECHO Autism program during the first 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…66 The Extension for Community Healthcare Outcomes model has also been used to promote best primary care practices by connecting autism specialists with primary care providers in remote areas of the world. 67…”
Section: The Importance Of Transitionsmentioning
confidence: 99%
“…66 The Extension for Community Healthcare Outcomes model has also been used to promote best primary care practices by connecting autism specialists with primary care providers in remote areas of the world. 67…”
Section: The Importance Of Transitionsmentioning
confidence: 99%
“…Participants prefer shorter sessions to limit the demand on their caseload, however there is a delicate balance between time and curriculum content. ECHO sessions worldwide vary from 60-120 minutes (30)(31)(32); further research could seek to explore the impact of session length on attendance, particularly if a shorter session improves attendance due to reduced time/staffing pressures. Although ECHO sessions place demands on time, the methodology means that there is no need to travel for training generating a potential overall time saving.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, only collecting post-assessment data makes it difficult to accurately assess the impact of the specialized training program. In addition, many of the included studies relied solely on participants’ self-assessment of their knowledge, self-efficacy, or practice behavior (Giachetto et al, 2019; Havercamp et al, 2016; Hine et al, 2021; Mazurek et al, 2019; Pasco et al, 2014; Swanson et al, 2014). In these studies, the lack of an objective assessment to measure the outcomes of interest means that the data are subject to bias from participants’ perceptions and may not be an accurate measure of the program’s impact.…”
Section: Discussionmentioning
confidence: 99%
“…While one study had participants attend bimonthly ECHO clinic meetings for a year (Mazurek et al, 2019), another had trainees attend weekly ECHO clinic meetings for three months (Mazurek, Stobbe, et al, 2020). Despite the variations in training duration and frequency, all of the studies that utilized the ECHO training model reported some level of positive outcomes (Bellesheim et al, 2020;Giachetto et al, 2019;Mazurek et al, 2019;Mazurek, Stobbe, et al, 2020); however, not all of the studies showed the same level of success. For example, two of the three ECHO studies that measured knowledge and self-efficacy reported significant changes to both outcome measures (Giachetto et al, 2019;, but another was only able to significantly increase self-efficacy and had no impact on knowledge (Mazurek, Stobbe, et al, 2020).…”
Section: Study/participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation